Effects of surgical angiogenesis on segmental bone reconstruction with cryopreserved massive-structural allografts in a porcine tibia model - Visser, Noortje; Rezaie, Elisa S.; Friedrich, Patricia F.; Kotsougiani-Fischer, Dimitra; Shin, Alexander Y.; Bishop, Allen T. (Journal of orthopaedic research, 2019)
Cryopreserved bone allografts (CBA) used to reconstruct segmental bone defects provide immediate structural stability, but are vulnerable to infection, non-union and late stress fracture as the majority of the allograft remains largely avascular. We sought to improve the bone vascularity and bone formation of CBAs by surgical angiogenesis with an implanted arteriovenous (AV) bundle, using a porcine tibial defect model. Cryopreserved tibial bone allografts were transplanted in swine leukocyte antigen (SLA) mismatched Yucatan minipigs to reconstruct a 3.5 cm segmental tibial defect. A cranial tibial AV-bundle was placed within its intramedullary canal to induce angiogenesis. The AV bundle was patent in eight pigs and ligated in a control group of eight pigs. At 20 weeks neo-angiogenesis was evaluated by micro-angiography. Bone formation was measured by quantitative histomorphometry and micro-computed tomography. Seven of eight AV-bundles in the revascularized group were patent. One had thrombosed due to allograft displacement. Total vascular volume was higher in the revascularized allografts compared to the ligated group (p = 0.015). Revascularized allografts had increased levels of bone formation on the allograft endosteal surface compared to the ligated control group (p = 0.05). Surgical angiogenesis of porcine tibial CBAs by intramedullary implantation of an AV-bundle creates an enhanced autogenous neoangiogenic circulation and accelerates active bone formation on allograft endosteal surfaces.
Gesehen am 17.02.2020